KARAKTERISTIK BENTUK DAN TATA RUANG RUMAH TRADISIONAL SUKU KAJANG DI BENTENG SOMBAOPU MAKASSAR - Suci Qadriana Ramadhan (Jurnal PROYEKSI: Arsitektur dan Perencanaan, 2022)
Traditional house is a building whose method of construction, function, structure and facade has its own characteristics and is passed down from generation to generation. This study aims to determine the shape characteristics and layout of the Kajang in Fort Somba Opu. The method used is descriptive qualitative, namely describing the results of processing qualitative data. The type of activity carried out is observation activity to obtain observational data from the field, in this case at Fort Somba Opu, Makassar City. This activity examines one of the traditional buildings in that location, namely the Kajang Traditional House. Traditional architecture has consistency in terms of the physical building such as the selection of materials, ornaments, shapes and dimensions. This consistency comes from the form of community acceptance in the region. The conclusion obtained from this research is that the traditional Kajang house in Fort Somba Opu has characteristics that tend to be almost the same as the original traditional house in Tana Toa Kajang